THE IMPACT OF ECONOMIC GROWTH TOWARDS ENVIRONMENTAL DEGRADATION: THE EVIDENCE FROM HECKSCHER-OHLIN THEORY AND ENVIRONMENTAL KUZNETS CURVE HYPOTHESIS - Clarnce, Abby Christie; Karia, Abdul Aziz (Malaysian Journal of Business and Economics (MJBE), 2020)
In this paper, researcher intend to investigate the relationship between economic growth and environmental degradation using Ordinary Least Square (OLS), the proxy used for environmental degradation is carbon dioxide emission (CO_2). In this investigation, there are 102 countries chosen ranging from 1995 until 2014. To determine whether there are significant different between countries, researcher put extra effort by considering whether there is significant difference between the factor endowment towards the environmental degradation, whereby, the effort of segregating the data into two groups will help us to identify the significance different between K and L abundant. The empirical result revealed that there is no significant difference between factor endowment towards the environment degradation.